Studying the Reflection Spectra of the New Black Hole X-Ray Binary Candidate MAXI J1631-479 Observed by NuSTAR: A Variable Broad Iron Line Profile - Xu, Yanjun; Harrison, Fiona A.; Tomsick, John A.; Walton, Dominic J.; Barret, Didier; Garcia, Javier; Hare, Jeremy; Parker, Michael L. (Astrophysical Journal, 2020)
We present results from the Nuclear Spectroscopic Telescope Array observations of the new black hole X-ray binary candidate MAXI J1631-479 at two epochs during its 2018-2019 outburst, which caught the source in a disk dominant state and a power-law dominant state. Strong relativistic disk reflection features are clearly detected, displaying significant variations in the shape and strength of the broad iron emission line between the two states. Spectral modeling of the reflection spectra reveals that the inner radius of the optically thick accretion disk evolves from r(g) (statistical errors at 90% confidence level) from the disk dominant to the power-law dominant state. Assuming in the former case that the inner disk radius is consistent with being at the innermost stable circular orbit, we estimate a black hole spin of a* > 0.94. Given that the bolometric luminosity is similar in the two states, our results indicate that the disk truncation observed in MAXI J1631-479 in the power-law dominant state is unlikely to be driven by a global variation in the accretion rate. We propose that it may instead arise from local instabilities in the inner edge of the accretion disk at high accretion rates. In addition, we find an absorption feature in the spectra centered at 7.33 0.03 keV during the disk dominant state, which is evidence for the rare case that an extremely fast disk wind (
CRIS-Team WoS Importer:2020-05-02